Diphyllobothriasis, Brazil - Mello Sampaio, Jorge Luiz; Piana de Andrade, Victor; Lucas, Maria da Conceição; Fung, Liang; Gagliardi, Sandra Maria B.; Santos, Sandra Rosalem P.; Figueiredo Mendes, Caio Marcio; Eduardo, Maria Bernadete de Paula; Dick, Terry (My University, 2005)
Cases of human diphyllobothriasis have been reported worldwide. Only 1 case in Brazil was diagnosed by our institution from January 1998 to December 2003. By comparison, 18 cases were diagnosed from March 2004 to January 2005. All patients who became infected ate raw fish in sushi or sashimi.
Keywords: adolescent; adult; animal tissue; Brazil; clinical article; diphyllobothriasis; Diphyllobothrium latum; fish; human; nonhuman; parasite examination; parasite prevalence; raw food; symptomatology; travel; Adolescent; Adult; Animals; Diphyllobothriasis; Diphyllobothrium; Female; Food Contamination; Food Parasitology; Humans; Intestinal Diseases, Parasitic; Ovum; Perciformes; Salmo salar; Seafood